Formulasi Susu Pengganti dan Evaluasi Pengaruhnya terhadap Performa Anak Domba Kembar - Asep Sudarman; Harun Fatmiati; Lilis Khotijah (Jurnal Sain Peternakan Indonesia, 2019)
The purpose of this experiment was to formulate and evaluate milk replacer on the production performance of twin lambs from before weaning to one month after weaning. Three pairs of twin lambs aged two weeks with a body weight of 3.83 ± 0.4 kg were divided into two groups, each consisting of three lambs. The treatments applied were PSI = lamb given mother's milk and PMR = lamb given milk replacer. Pre-weaning dry matter consumption data were analyzed descriptively and other data were analyzed using the T-test. The results showed that the dry matter consumption lambs that were given milk replacers in pre-weaning was 164.18 ± 31.25 g/head/day with the largest proportion coming from milk replacers (61.4%). PSI group lambs had dry matter and energy consumption after weaning, daily gain before and after weaning, and body weight when weaned were significantly higher (P <0.05) than the PMR group lambs. However, the ratio of feed conversion and body weight at 90 days in the two groups of lamb were not significantly different. All lambs were healthy and no one died. It is concluded that formulated milk replacer provides production performance in lambs that are equivalent to lambs fed with mother's milk.